Analisis Potensi Preferensi dan Persepsi Masyarakat Desa Bintais Julu terhadap Sikap pada Asuransi Syariah - Yuli Anisyah Hasibuan; Zuhrinal M. Nawawi; Reni Ria Armayani (Universitas 45 Surabaya, 2024)
This research aims to determine the influence of the Potential, Preferences and Perceptions of the Bintais Julu Village Community on Attitudes towards Sharia Insurance. This type of research uses quantitative research methods. Data collection was carried out by distributing questionnaires to the Bintais Julu Village Community. The sampling technique in this research was to use the Cluster Sampling technique and the number of samples used was 72 respondents. Data analysis uses validity, reliability, classical assumptions, multiple linear regression, t, f, and coefficient of determination tests using the SPSS version 23 program. The partial research results show that the potential variable has no significant effect on the attitudes of the people of Bintais Julu Village, with a t value of -1.711 < t table 1.995 and a significance value of 0.092 > 0.05. Meanwhile, for the preference variable, it is known that tcount is 2.926 > ttable 1.995 and the significance value is 0.005 <0.05. As well as the perception variable, it is known that tcount is 0.836 > ttable 1.995 and the significant value is 0.406 <0.05, which means that the preference variable has a partially significant positive effect on the attitudes of the people of Bintais Julu Village. Meanwhile, the research results simultaneously show potential and perception variables, and do not have a significant effect on the attitude of the people of Bintais Julu Village towards Sharia Insurance, with a fcount value of 4.506 > ftable 2.74 and a significance value of 0.006 < 0.05.